2020
DOI: 10.1126/sciadv.abb9110
|View full text |Cite
|
Sign up to set email alerts
|

The biophysical, molecular, and anatomical landscape of pigeon CRY4: A candidate light-based quantal magnetosensor

Abstract: The biophysical and molecular mechanisms that enable animals to detect magnetic fields are unknown. It has been proposed that birds have a light-dependent magnetic compass that relies on the formation of radical pairs within cryptochrome molecules. Using spectroscopic methods, we show that pigeon cryptochrome clCRY4 is photoreduced efficiently and forms long-lived spin-correlated radical pairs via a tetrad of tryptophan residues. We report that clCRY4 is broadly and stably expressed within the retina but enric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
85
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(89 citation statements)
references
References 51 publications
3
85
0
1
Order By: Relevance
“…Based on studies with purified Cry1, Kutta et al (2017) questioned whether vertebrate Cry1 indeed had FAD bound and hence could be photo-reduced (see also Hochstoeger et al, 2020 ), although Liedvogel et al (2007) reported that avian Cry 1a contained FAD and could absorb blue light. An in vivo study also showed that at least avian Cry1a is directly activated by light (see Figure 5 ).…”
Section: Cryptochromes In the Avian Eyesmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on studies with purified Cry1, Kutta et al (2017) questioned whether vertebrate Cry1 indeed had FAD bound and hence could be photo-reduced (see also Hochstoeger et al, 2020 ), although Liedvogel et al (2007) reported that avian Cry 1a contained FAD and could absorb blue light. An in vivo study also showed that at least avian Cry1a is directly activated by light (see Figure 5 ).…”
Section: Cryptochromes In the Avian Eyesmentioning
confidence: 99%
“…This splice product appears to be widespread; by genomic BLAST database search, it was also indicated in more than 25 avian species of various orders ( Einwich et al, 2020 ). Another study localized Cry4 also in the outer plexiform layer, where it seemed associated with the synapses between photoreceptors and horizontal cells ( Hochstoeger et al, 2020 ).…”
Section: Cryptochromes In the Avian Eyesmentioning
confidence: 99%
See 2 more Smart Citations
“…Zeitaufgelöste EPR und magnetfeldabhängige transiente Absorptionsspektroskopie deuten daraufhin, dass eine solche Navigation der Tiere durch den magnetfeldabhängigen Radikalpaar-Mechanismus möglich sein könnte. 40,41) In-situ-EPR Mit der EPR-Spektroskopie lassen sich chemische Reaktionen auch in situ verfolgen, was Aussagen über die Reaktionsdynamik im Zentrum solcher Arbeiten ermöglicht. Im Zentrum stehen katalytische Reaktionen.…”
unclassified